Extending Campus Network Via Intranet and IP-Telephony For Better Performance and Service Delivery: Meeting Organizational Goals - Ojugo, Arnold Adimabua; Eboka, Andrew Okonji (Yayasan Ahmar Cendekia Indonesia, 2019)
The adoption of information and communication technology (ICT) tools and medium in today’s business, is geared to advance data processing tasks, timely exchange of data, easy access to the Internet at increased speed, extended memory to house large volumes of data, and better communications, etc. Businesses grow in lieu of advancing the services they offer; But, they require as a matter of urgency, a corresponding need for effective communication to grow exponentially. The Intranet provides an option to advance such via its many features (not limited to) collaborative communication channel, ease in business processes, etc. We posit that many businesses lack a clear strategy to implement an effective Intranet design. This often leads to investment profit loss, loss of time, unproductivity, and complete failure in achieving its set goals. Extending Ojugo and Eboka (2020) via a multi-service intranet, the study outcomes an infrastructure that allows the effective integration of data solutions via an open-source protocol, application, hardware, and software. Three common issues observed therein includes: packet loss, jitters, and latency. Jitters and packet loss can be resolved via increased bandwidth allocation; while, latency is minimized via upgrade in the infrastructure. Thus, our proposed solution seeks to provide users with mobility, resilience, economy, flexibility, and productivity with improved service delivery and performance. The study recommends that to harness the full benefits of Intranet and improve communication within businesses and organizations today, there is the need for a constant knowledge update is imperative, which will in turn improve effective communication in the implemented infrastructure.